2010
DOI: 10.1007/s00044-010-9343-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, antimicrobial, and DNA cleavage studies of metal complexes of coumarin Schiff bases

Abstract: Co(II), Ni(II), Cu(II), and Zn(II) complexes of the Schiff bases formed by the condensation of 8-formyl-7-hydroxy-4-methyl-coumarin with 3-amino-pyridine (L 1 ) and 3-amino-2-chloro-pyridine (L 2 ) are synthesized and characterized by various physico-chemical methods. The FAB-mass spectra of the ligand L 1 and its Zn(II) complex are reported herewith. Thermal studies with Co(II) and Ni(II) complexes of both the ligands L 1 and L 2 are also reported. From the above studies, it is concluded that the ligand L 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Three ligand approaches are suggested [19][20][21][22]: transporters, which provide metal transport to infection, carriers which provide metal transport and its gradual delivery, multifunctional ligands, that can act as transporters, carriers and antibiotics or analgetics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Three ligand approaches are suggested [19][20][21][22]: transporters, which provide metal transport to infection, carriers which provide metal transport and its gradual delivery, multifunctional ligands, that can act as transporters, carriers and antibiotics or analgetics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…(fig.7). There are several reports were also cited for Co(II) and Cu(II) complexes showing better bioactivities [29]. Moreover, the heterocyclic Schiff bases having the different functional group to interact with nucleoside bases with greater tendency even after complexation with metal ions.…”
Section: X-ray Diffraction:-mentioning
confidence: 99%
“…Moreover, previously reported coumarin Schiff bases and their metal complexes were shown to exhibit outstanding luminescence (Datta et al 2011) which may be advantageous for application of related compounds as probes. Other studies revealed that the coumarin derivatives interact strongly with DNA and can cause DNA cleavage (Phaniband et al 2011;Kulkarni et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Another example involves quinoline with 4(N,N)-dimethylthiosemicarbazone which produced a novel water-soluble sulphur-bridged binuclear copper(II) complex (Senthil Raja et al 2011). Coumarin derivatives, such as 3-acetylcoumarin opted for in this work, are attractive because of their wide variety of antioxidant, antibacterial, antifungal and cytotoxic activities (Datta et al 2011;Bagihalli et al 2008;Phaniband et al 2011;Kulkarni et al 2009;Creaven et al 2009). Moreover, previously reported coumarin Schiff bases and their metal complexes were shown to exhibit outstanding luminescence (Datta et al 2011) which may be advantageous for application of related compounds as probes.…”
Section: Introductionmentioning
confidence: 97%